Falling monuments, reluctant ruins : the persistence of the past in the architecture of apartheid - Judin, Hilton (Wits University Press, 2021)
This edited collection looks at ruins and vacant buildings as part of South Africa's oppressive history of colonialism and apartheid and ways in which the past persists into the present.